PENGEMBANGAN KEMAMPUAN PEMAHAMAN DAN KOMUNIKASI MATEMATIS SISWA SEKOLAH DASAR MELALUI PEMBELAJARAN GEOMETRI BERBASIS TEORI VAN HIELE - Nuraeni, Epon (2010)
This study is a pre test- post test experimental control group design conducted to investigate the role of teaching learning geometry process based on Van Hiele's theory and school level on students' concept understanding and mathematical communication abilities. The subjects of this study were 158 fifth grade from three elementary school of high, medium, and low cluster in Tasikmalaya. Instruments of the study were a concept understanding test, a mathematical communication test, and an opinon scale. The data were analyzed by using two path anova, Scheffe test, and t-test. The study found that the rolef of teaching learning geometri process based on Van Hiele' theory is superior compare to the role of conventional approach, and the role of school level on achieving and gaining the students' concept understanding and mathematical communication abilities. That superiority is supported by some findings namely: 1) Students' concept understanding ability of teaching learning process based van Hiele' theory class is classified as medium and are on high level of visualization, low level of analysis, and low level of informal deduction, while that ability of students in conventional class is classified as low and on low level of visualization; 2) Students' mathematical communication of teaching learning process based van Hiele' theory class is classified as high, while that ability of students of conventional class is classified as low; 3) The higher the school level it is found the higher students' concept understanding and mathematical communication abilities as well; 4) However, students' concept understanding and mathematical communication abilities of low and medium school levels taught by teaching learning process based van Hiele's theory are higher than those of students' abilities of conventional class. Moreover, the study found that: 1) There are no interaction between teaching learning process and school level on concept understanding and mathematical communication abilities; 2) There is medium assosiation between concept understanding and mathematical communication abilities, and 3) Students perform positive opinion on teaching learning geometry process based on Van Hiele's theory